Relationship Between Upper Limb Injuries and Hip Range of Motion in Elementary and Junior High School Baseball Players. Issue 2 (10th February 2021) - Hamano, Noritaka; Shitara, Hitoshi; Tajika, Tsuyoshi; Kuboi, Takuro; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Kitagawa, Takanori; Kobayashi, Hiroki; Yamamoto, Atsushi; Kobayashi, Tsutomu; Takagishi, Kenji; Chikuda, Hirotaka; et al.
Background: Shoulder and elbow injuries are major problems in baseball players. Tightness of the upper extremities has been reported as a risk factor for shoulder and elbow injuries in elementary and junior high school baseball players. However, few studies have been conducted on the relationship between decreased hip range of motion (ROM) and shoulder and elbow injuries. Purpose/Hypothesis: This study aimed to prospectively examine the relationship between hip ROM and throwing-related shoulder and elbow injuries in elementary and junior high school baseball players. The hypothesis was that players with unrestricted ROM in the hip would have a reduced risk of upper extremity injuries. Methods: The study included 263 baseball players (mean ± SD age, 10.5 ± 1.3 years; range, 7-14 years). The following physical parameters were assessed: (1) hip flexion ROM measured in the supine position and (2) hip internal and external rotation in the prone position. After the season, players completed questionnaires regarding shoulder and/or elbow injuries. For comparison, the players were classified as injured (not able to play for ≥8 days because of shoulder and/or elbow problems) or noninjured. Results: During the season, 52 players had shoulder and/or elbow injuries. When the injured and noninjured groups were compared, hip flexion on the dominant side (121.5° ± 12.0° vs 126.7° ± 9.8°, respectively; P < .01), hip flexion on the nondominant side (119.6° ± 11.7° vs 126.0° ± 9.9°, respectively; P < .01), and internal rotation on the dominant side (52.5° ± 11.3° vs 56.8° ± 10.8°, respectively; P = .01) were significantly reduced in the injured group. Conclusion: We identified preseason decreases in flexion bilaterally and internal rotation on the dominant side as risk factors for shoulder and elbow injuries in elementary and junior high school baseball players. Further studies are required to prevent disabilities in elementary and junior high school baseball players through development of prevention and intervention programs.